Painters of the Mind's Eye : Belgian Symbolists and Surrealists. - Legrand, Francine-Claire (Brussel : Ministerie van de Franse Cultuur, 1974)
Rops, Félicien ; Spilliaert, Léon ; Wiertz, Antoine ; Delville, Jean ; Khnopff, Fernand ; Mellery, Xavier ; Delvaux, Paul ; Magritte, René
Painters of the Mind's Eye : Belgian Symbolists and Surrealists, The New York Cultural Center in association with Fairleigh Dickinson University, New York, 1-2/17-3-74 ; The Museum of Fine Arts, Houston, 4-4/12-5-74
boek
Keywords: België